2016
DOI: 10.1074/jbc.m116.715508
|View full text |Cite
|
Sign up to set email alerts
|

Complex Formed between Intramembrane Metalloprotease SpoIVFB and Its Substrate, Pro-σK

Abstract: Intramembrane metalloproteases (IMMPs) are conserved from bacteria to humans and control many important signaling pathways, but little is known about how IMMPs interact with their substrates. SpoIVFB is an IMMP that cleaves Pro-K during Bacillus subtilis endospore formation. When catalytically inactive SpoIVFB was coexpressed with C-terminally truncated Pro-K (1-126) (which can be cleaved by active SpoIVFB) in Escherichia coli, the substrate dramatically improved solubilization of the enzyme from membranes wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 75 publications
2
13
0
Order By: Relevance
“…The cross-linking results supported the model of SpoIVFB and provided initial insight into its interaction with Pro-σ K (1-127) (25). Biochemical approaches showed that the SpoIVFB-Pro-σ K (1-127) complex can be solubilized from E. coli membranes with mild detergents and purified (26). Disulfide cross-linking of purified complex containing single-Cys versions of the two proteins suggested that it resembles the complex formed in vivo.…”
Section: Significancesupporting
confidence: 60%
See 4 more Smart Citations
“…The cross-linking results supported the model of SpoIVFB and provided initial insight into its interaction with Pro-σ K (1-127) (25). Biochemical approaches showed that the SpoIVFB-Pro-σ K (1-127) complex can be solubilized from E. coli membranes with mild detergents and purified (26). Disulfide cross-linking of purified complex containing single-Cys versions of the two proteins suggested that it resembles the complex formed in vivo.…”
Section: Significancesupporting
confidence: 60%
“…Side chains of residues in the two regions may directly interact, although the Ala substitutions could subtly change SpoIVFB structure and indirectly perturb other interactions with Pro-σ K . Disulfide cross-linking of single-Cys versions of SpoIVFB and Pro-σ K , both in E. coli (25) and in vitro (26) in the presence or absence of ATP, should further elucidate how the SpoIVFB linker mediates ATP-dependent coordination between the CBS and membrane domains.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations